Seasonal dynamics and impact of P fertilizer treatments and cover crops on soil health indicators in a no-till corn-soybean system - Pasket, Amber Marie (Kansas State University, 2023)
While phosphorus (P) is an essential nutrient from crop growth, it can be one of the most limiting nutrients in crop production as it is relatively immobile in soil. Therefore, P amendments (such as synthetic fertilizer or animal manure) are needed to meet crop P demand. The overapplication of P can lead to adverse environmental conditions, namely eutrophication. Soil testing prior to nutrient applications is important as it defines the agronomic need for nutrient applications to support crop yields while reducing the risks of overapplication. Soil testing laboratories use two different approaches to make P fertilizer recommendations. The build and maintain (BAM) approach builds soil test P to a critical level then maintains soil test P in a target range with subsequent fertilizer applications. In the sufficiency (SUF) approach, a critical level of soil test P is determined to achieve 90-95% maximum yield, and P is only applied when a crop response is expected. In efforts to improve soil health, conservation practices such as no-till management or the implementation of cover crops can be introduced into a cropping system. Soil health indicators are measurable properties of soil that can provide insights on how well the soil can function. In addition, seasonal dynamics of soil health indicators are widely inconsistent in literature due to differences in climate, cover crops, crop rotations, and tillage practices. As a consequence of the seasonal dynamics of soil health indicators, especially for biological indicators, recommendations of the correct time to soil sample are difficult. A study was initiated in 2020 to determine the effects of cover crop and P fertilizer treatment impacts on biological soil heath indicators and to assess the seasonal dynamics of these indicators during a growing season. This study occurred at the Kansas Agricultural Watershed (KAW) site near Manhattan, KS. The site is a 2x3 randomized complete block design in a no-till corn (Zea mays)-soybean (Glycine max) rotation that is replicated three times. There were three levels of P fertilizer managements; treatments under BAM and SUF managements and a no P/control (NP) treatment. There were two levels of cover crop treatments; the presence (CC)/absence (NC) of a cereal rye (Secale cereale) cover crop. During the three-year duration of the experiment, ammonium polyphosphate was added to the BAM treatment at maintenance rates of 17, 31, and 54 kg P₂O₅ ha⁻¹ in 2020, 2021, and 2022, respectively. No P has been applied to the SUF treatment since December 2018, therefore, the SUF treatment has been in a P draw down phase during the duration of this experiment. No P had been applied to the NP treatment since 2014. Nitrogen (N) applications were not balanced in 2020 and 2022. As a result, only the BAM treatment received N fertilizer through the ammonium polyphosphate application in 2020 and 2022. Composite soil samples were collected (0-5 cm) six times during the 2021 and 2022 growing season. Sampling times included a sampling prior to cover crop termination, four sampling during crop growth, and one sampling post-harvest. Soil health indicators measured were microbial biomass carbon (C), N, and P, inorganic N, dissolved total N, dissolved organic N, autoclaved citrate extractable (ACE) protein, citrate-extractable P, four soil enzyme activities ([beta]-glucosidase, [beta]-glucosaminidase, and acid and alkaline phosphatase), soil respiration, active C, and dissolved organic C. Significant P fertilizer treatment by sampling time interactions were observed for N pools in both years, likely due to differences in soil moisture and temperature, crop N uptake, biological transformations of N, and fertilizer applications. There was a significant cover crop by sampling time interaction for dissolved total N and NO₃-N in 2022. Cover crops reduced dissolved total N and NO₃-N concentrations during the first two sampling times when a cover crop was still living and when the cover crop had been terminated three days prior. It was likely that cereal rye was able to scavenge N from the soil and assimilate N into the biomass, reducing the risk of N loss through leaching. Cover crops influenced C pools and measures of microbial function and activity in both years. Cover crops likely provided additional above- and belowground inputs that increased substrate availability to the soil microbial community. In addition, a significant P fertilizer by cover crop interaction was observed for alkaline phosphatase in 2021 and 2022 and glucosidase in 2022. The presence of a cover crop significantly increased enzyme activity in the NP and SUF treatment, likely reflecting increased nutrient cycling in system at the margins of deficiency. Sampling time influenced most soil health indicators in both years, however, the lack of cover crop by sampling time interactions for most soil health indicators observed in either year likely reflect that other environmental factors such as precipitation and temperature were the primary driver of seasonal trends of soil health indicators. Although no-till management can improve soil health, nutrient stratification can lead to decreased microbial activity in the subsurface. In order to assess the effect of sample depth (as well as cover crop and P fertilizer treatment) on selected soil health indicators, soil samples were also collected at 0-5, 5-10, and 10-15 cm post-harvest in 2020, 2021, and 2022. Soil health indicators assessed included active C and ACE protein, soil respiration, and four soil enzyme activities ([beta]-glucosidase, [beta]-glucosaminidase, and acid and alkaline phosphatase). Sampling depth significantly influenced all soil health indicators in all three years. Nutrient pools and measures of microbial activity were significantly higher at 0-5 cm compared to 5-10 and 10-15 cm, reflecting nutrient stratification at the study site. Phosphorus availability significantly influenced soil protein concentrations in all three years. Cover crop biomass production and well as precipitation and temperature conditions during the three harvest years likely resulted in inconsistent cover crop effects on soil health indicators. Only soil respiration was significantly increased by cover crop presence in all three years of this study. The overall results of this study, highlight the potential to improve nutrient cycling by cover crop implementation. Cover crops can promote the soil microbial community to meeting the challenges of meeting crop nutrient demand while minimizing nutrient loss by managing a nutrient such as P closer to the margins of deficiency.
Keywords: Phosphorus; Cover crops; Soil health